Employment Effects of Labour Taxation in an Efficiency Wage Model with Alternative Budget Constraints and Time Horizons - Laszlo Goerke (Institute for the Study of Labor (IZA), 2000)
In an efficiency wage economy with variable profits, a shift from payroll to employment taxes will reduce unemployment if the tax level is held constant at the initial wage. However, unemployment will rise if firms are constrained to zero profits in the long-run and if tax revenues are constant. This reversal of employment effects occurs because the shift in taxes reduces wages. This implies a budget deficit. Hence, taxes will have to be raised if revenues are held constant. If the firm's profits cannot change, the tax increase will cause some firms to close down and unemployment will rise. Thus, the predicted employment consequences of changes in the tax structure depend on assumptions about the time-horizon and budget constraint.
Keywords: J32; H22; J41; H25; 330; Efficiency wages; long-run; short-run; labour taxes; Lohnsummensteuer; Lohnsteuer; Steuerwirkung; Effizienzlohn; Beschäftigungseffekt; Öffentlicher Haushalt; Theorie